Restructuring a Myth : Economic Impact of Casinos in the Chippewa Valley - Chase, Lisa Ann (My University, 2012)
In 1988 the United States Congress passed the Indian Gaming Regulatory Act, which made gaming possible. It would not be until 1992 that the St. Croix Band of Chippewa Indians would open the door to their first casino in Turtle Lake, Wisconsin. This study will help fill in the gaps of missing economic literature of the Wisconsin St. Croix tribe.
Color poster with text, maps, and images.
Keywords: Gambling on Indian reservations--Wisconsin--Turtle Lake; Turtle Lake (Wis.)--Economic conditions; Posters